2000
DOI: 10.3109/10428190009065832
|View full text |Cite
|
Sign up to set email alerts
|

Association of Burkitt's Lymphoma with the Epstein-Barr Virus in Two Developing Countries

Abstract: The clinical presentation of Burkitt's lymphoma (BL) and it's association with the Epstein-Barr virus (EBV) varies in different geographic areas, BL in developing countries being "intermediate" between the sporadic and endemic types, both in it's clinical presentation and it's association with EBV, which varies from 25-80%. In this study we have analysed the clinical features, EBV association, subtype and prevalence of the deleted variant of the Latent Membrane Protein-1 (LMP-1) of EBV in forty-two cases from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
3
23
1
Order By: Relevance
“…Although the sample size was small, the findings in the present study were similar to results reported in the previous studies in Japan [Kunimoto et al, 1992;Fukayama et al, 1994;Sidagis et al, 1997]. Among EBV-associated-Burkitt's lymphoma in India, subtype A was predominant [Rao et al, 2000]. On the other hand, Rathaur et al [1999] reported a geographical variation of EBV subtypes among Indian patients with nasopharyngeal carcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…Although the sample size was small, the findings in the present study were similar to results reported in the previous studies in Japan [Kunimoto et al, 1992;Fukayama et al, 1994;Sidagis et al, 1997]. Among EBV-associated-Burkitt's lymphoma in India, subtype A was predominant [Rao et al, 2000]. On the other hand, Rathaur et al [1999] reported a geographical variation of EBV subtypes among Indian patients with nasopharyngeal carcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…These results were in agreement with some previously studies which also found 30% EBV positive in their NHL cases [22], [26]. On other hand, different studies reported higher association of the EBV with NHL as high as 80% in other developing countries [27], [10]. It is also worth mentioning that Burkitt's lymphoma is a high-grade malignant NHL that is most commonly associated with EBV infection [10], [12], [22], [27].…”
Section: Resultssupporting
confidence: 82%
“…On other hand, different studies reported higher association of the EBV with NHL as high as 80% in other developing countries [27], [10]. It is also worth mentioning that Burkitt's lymphoma is a high-grade malignant NHL that is most commonly associated with EBV infection [10], [12], [22], [27]. Furthermore, in Africa, Burkitt's lymphoma is associated with Plasmodium falciparum malaria, and tumors usually present in the jaw, over 90 percent of these cases are associated with EBV.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in cancer incidence rates between HIC and many LIC have been documented for childhood cancer as a whole, [5][6][7] and for a variety of specific cancers, including Burkitt and Hodgkin lymphomas, [8][9][10] adrenocortical carcinoma, 11,12 and acute lymphoblastic leukemia (ALL), the most common childhood cancer worldwide. International variation in the incidence of ALL is well recognized.…”
Section: Sources and Quality Of Childhood Cancer Epidemiology Datamentioning
confidence: 99%